2020
DOI: 10.12982/cmujns.2020.00020
|View full text |Cite
|
Sign up to set email alerts
|

Community Perceptions of Free-Roaming Dogs and Management Practices in Villages at the Periphery of a Protected Area in Bhutan

Abstract: In Bhutan, free-roaming dogs pose health hazards to human, livestock, and wildlife. Understanding the perceptions and practices of local communities regarding free-roaming dogs is important to mitigate negative impacts. A community-based study was conducted in the buffer zone of Strict Nature Reserve, western Bhutan. The study was conducted in February-October 2018 using a household questionnaire survey, 'free-listing' of dog diseases, group discussions and key-informant interviews. A total of 140 households f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The prevalence of CDV natural infection in highdensity domestic dog populations in our study area [29] emphasizes the risk of transmission among the domestic dog population, and of spillover infection to wild carnivores populations. In a previous study [30], we demonstrated that interactions between pet dogs and wildlife in an adjacent protected area of the study site were possible (Fig. 1).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The prevalence of CDV natural infection in highdensity domestic dog populations in our study area [29] emphasizes the risk of transmission among the domestic dog population, and of spillover infection to wild carnivores populations. In a previous study [30], we demonstrated that interactions between pet dogs and wildlife in an adjacent protected area of the study site were possible (Fig. 1).…”
Section: Discussionmentioning
confidence: 57%
“…This is a concern for wildlife conservation as it poses significant transmission risks to several endangered wild canid and felid species, as observed in studies conducted elsewhere [9,31,32]. Farmers from the study site area reported observing frequent interactions between domestic dogs and wildlife, mostly at the periphery of agriculture land, and there is evidence of freeroaming dogs attacking Himalayan black bear in the study area [30].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The role of animal control/field services is to “provide a wide array of services to their communities, including saving pets in danger, protecting human health and safety, enforcing laws and ordinances, providing support and education to community members, disaster response, helping lost pets get home, and helping wildlife, livestock, and exotic animals, in addition to cats, dogs, and other pets” [ 39 ]. Free-roaming dogs fall within the purview of animal control/field services due to the ongoing discussion in the veterinary epidemiology and public health fields about the potential risk of free-roaming dogs to community health [ 14 , 15 , 16 , 17 ]. This discussion includes their negative impacts on native and endemic wildlife, they are common vectors for disease transmission (rabies, parvovirus, parasites, and canine distemper virus), and can be perpetrators of aggression towards humans [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a critical need to address concerns regarding free-roaming dogs’ impact on community health and safety (e.g., dog bites, aggressive behavior, food competition or predation on native and endemic wildlife, livestock predation, and zoonotic disease) [ 2 , 12 , 13 , 14 , 15 , 16 , 17 ]. Current management strategies have been limited by their inability to address the complex social, cultural, and structural factors that have informed historical and present practices related to free-roaming dogs.…”
Section: Introductionmentioning
confidence: 99%